Physicochemical and Functional Characterization of Female Reproductive Fluids: A Report of the First Two Infants Born Following Addition of Their Mother's Fluids to the Embryo Culture Media - Canha-Gouveia, Analuce; Prieto-Sánchez, Maria Teresa; Sánchez-Ferrer, Maria Luisa; Mollá, Marta; Martínez-Soto, Juan Carlos; París-Oller, Evelyne; Soriano-Úbeda, Cristina; Landeras, José; Coy, Pilar (Frontiers in Physiology, 2021)
Culture media supplemented with reproductive fluids (RF) have been used in livestock species, improving the efficiency and quality of in vitro produced embryos. However, usefulness in humans is still unknown. In this study, we collected human reproductive fluids (HRFs) ex vivo (from 25 patients undergoing abdominal hysterectomy plus bilateral salpingectomy) and in vivo (from 31 oocyte donors). Afterward, protocols to evaluate their osmolality, pH, total protein concentration, endotoxin level, and sterility were optimized, establishing security ranges for their use as natural additives. In addition, a functional assay was developed with bovine embryos grown in vitro in a medium supplemented with 1% of collected HRFs. Finally, a proof of concept was performed with six patients on post ovulation day 2 to evaluate the full-term viability of embryos grown in media supplemented with autologous uterine fluid, collected under in vivo conditions. Two of the embryos resulted in successful pregnancy and delivery of healthy babies. In conclusion, this study establishes a complete quality control sheet of HRFs as additives for embryo culture media and shows first preliminary data on obtaining healthy offspring derived from embryos grown in media supplemented with HRFs.